2004
DOI: 10.1007/s10072-004-0314-4
|View full text |Cite
|
Sign up to set email alerts
|

Migraine, daily chronic headache and fibromyalgia in the same patient: an evolutive ?continuum? of non organic chronic pain? About 100 clinical cases

Abstract: Aim of this study is to evaluate if migraine, daily chronic headache and fibromyalgia in the same patient can be considered as an evolutive continuum of non organic chronic pain. Therefore, migraine, daily chronic headache and fibromyalgia should be considered the expression of chronic antinociceptive system alteration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 2 publications
2
14
0
3
Order By: Relevance
“…For this reason, we investigated the incidence of fibromyalgia in our study cohort and found none. There is a very high incidence (53‐82%) of headache among fibromyalgia patients, which is reportedly either migraine or tension‐type headaches 18,19 . Conversely, 24‐48% of headache patients also have fibromyalgia 20 .…”
Section: Resultsmentioning
confidence: 99%
“…For this reason, we investigated the incidence of fibromyalgia in our study cohort and found none. There is a very high incidence (53‐82%) of headache among fibromyalgia patients, which is reportedly either migraine or tension‐type headaches 18,19 . Conversely, 24‐48% of headache patients also have fibromyalgia 20 .…”
Section: Resultsmentioning
confidence: 99%
“…Fibromyalgia is observed in 22-36% of migraine patients (10,19). It has been hypothesized that episodic migraine and fibromyalgia belong to the same disorder (19,20) and that a common mechanism underlies the widespread hypersensitivity in fibromyalgia and migraine patients. Cephalic and extracephalic allodynia exhibit different features, with the former being mostly mechanical (92% of patients) and the latter thermal (75% of patients).…”
Section: Discussionmentioning
confidence: 99%
“…Common genetic basis, synergetically working with other factors (emotional, personality features, stressful events and medication overuse) should cause a chronic antinociceptive system alteration and therefore a progressive increase (hyperalgesia) and diffusion (panalgesia) of pain. It has been hypothesized that episodic migraine, chronic daily headaches and FM may actually be a continuum of the same disorder [5].…”
Section: Introductionmentioning
confidence: 99%